Dynamic footprint for stabilising a hygiene chair - Olsson,Martin; Åberg,Elias (2022)
The purpose of this thesis work is to investigate whether a dynamic chassis can possibly enhance hygiene chairs used in hospitals and elderly care. The problem with a lot of today’s products is the difficulty of manoeuvring the hygiene chair in tight spaces, and to allow for a high enough seating position to contribute to a more ergonomic working position for caregivers during showering. Thereof it is interesting to investigate if one can decrease the chassis size of the hygiene chair in tight spaces, but also to increase the chassis size in a raised chair position for increased stability. The project is seen as a pre-study for coming development work regarding the company’s hygiene chairs. The project has followed a development process inspired by methodology described by Ulrich and Eppinger in their book Product Design and Development, combined with elements of agile development methodology. The goal was to develop a wide range of concept ideas which acts as a foundation for further development, where also one or a couple of alternatives could be further developed with prototyping. Many interesting concept suggestions of dynamic chassis have been generated and evaluated. The most suitable concept has been further developed and tested physically through the making of a full-scale prototype. To summarise, this thesis work has shown concept suggestions with good potential to increase the stability of hygiene chairs by utilising a dynamic chassis, which can decrease its occupied space at low seating positions and increase the footprint in raised seating positions.
Keywords: Elderly care; Hygiene; Mechanical design; Concept development; Stability